Revolution in cancer treatment methods: Perspective review of factors affecting the final results of nanoparticles used in magnetic fluid hyperthermia - P. Rastgoo Oskoui; M. Rezvani (Health Sciences Review)
Recent advances in nanotechnology have made magnetic fluid hyperthermia a potential therapeutic platform for cancer treatment. Magnetic fluid hyperthermia can be used alone or in combination with other conventional therapeutic methods such as chemotherapy, radiotherapy, etc. In order to accurately control the temperature of cancerous tissue and prevent cell necrosis, it is necessary to identify and optimize the factors affecting the magnetic losses of nanoparticles. The type of nanoparticles, the size and shape of the particles, the type of solution used for dispersion, etc. are some of the factors that affect the rate of heat loss under alternating magnetic fields. In this review, the effect of various factors on the rate of heat generation has been briefly reviewed. Also, smart drug delivery systems based on drug release during temperature increase due to magnetic losses were investigated.